2021
DOI: 10.1177/2164956121989258
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Admission and Clinical Outcomes Among Patients Admitted to Medical Intensive Care Unit of a Teaching and Referral Hospital, Northwest Ethiopia

Abstract: Background The intensive care unit (ICU) is a health care delivery service for patients who are in critical condition with potentially recoverable diseases. Patients can benefit from more detailed observation, monitoring and advanced treatment than other wards or department. The care is advancing but in resource-limited settings, it is lagging far behind and mortality is still higher due to various reasons. Therefore, we aimed to determine the admission patterns, clinical outcomes and associated factors among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
34
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 19 publications
16
34
2
Order By: Relevance
“…In general, the proportion of mortality increased with increasing age, with the highest level of mortality seen among patients aged 80-99 years old (75%) and the lowest among patients aged 0-19 years old (16.7%). This agrees with the reports of a study carried out in Ethiopia, which reported the highest rate of mortality among patients more than 60 years old [ 18 ]. However, it opposes a previous study that found no association between old age and increased mortality [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, the proportion of mortality increased with increasing age, with the highest level of mortality seen among patients aged 80-99 years old (75%) and the lowest among patients aged 0-19 years old (16.7%). This agrees with the reports of a study carried out in Ethiopia, which reported the highest rate of mortality among patients more than 60 years old [ 18 ]. However, it opposes a previous study that found no association between old age and increased mortality [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is comparable to results from other parts of Nigeria, which reported ICU mortality rates of 34.6% and 40.8% in Calabar and Abakaliki, respectively [ 3 , 17 ]. Other African countries reported ICU mortality rates ranging from 38.7% to 40.1% [ 14 , 18 , 19 ]. However, these are comparatively higher than the findings in more developed nations including the Scandinavian countries (Finland, Norway, and Sweden) (9.1%) and the United States of America (11.3%) [ 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rate of the ICU was 45.8 %. This is in congruent with studies reported from Ethiopia and Nigeria ( 2 – 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present review, the median age was in the third decades with proportional male to female ratio and median ICU admission was three days. These results were consistent with prior reports from other referral hospitals in Ethiopia ( 1 , 2 ). The overall mortality rate of the ICU was 45.8 %.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation